Training volume and total energy expenditure of an Olympic and Ironman world champion: approaching the upper limits of human capabilities - Das, M. S.; Bu, O. A.; Sandbakk, Ø.; Rønnestad, B. R.; Plasqui, G.; Gundersen, H.; Kristoffersen, M. (Journal of Applied Physiology, 2024)
Research on world-class athletes in endurance events, such as cycling Grand Tours, has reported extreme levels of total energy expenditure. However, it has been argued that over extended periods, such as months, sustained energy expenditure is capped at approximately 2.5 times the basal metabolic rate. Triathlon is particularly notable for its high energetic demands due to its multimodal nature, requiring athletes to maintain high training volumes. In this case study, we analyzed the total energy expenditure of world-class triathlete Kristian Blummenfelt using doubly labeled water over two specific periods, along with 3 yr of training data. Total energy expenditure ranged from 7,019 to 8,506 kcal/day. Reported energy intake ranged from 4,899 to 6,360 kcal/day. The annual training volumes for the years 2020-2022 were 1,480, 1,350, and 1,308 h, respectively, following a pyramidal intensity distribution. Approximately 53% of the entire three-year period matched with the doubly labeled water measurement periods in terms of training volume, indicating that the recorded total energy expenditure is representative of the majority of the observed data. Hence, the greater part of the 3-yr period likely exceeds the proposed metabolic ceiling for sustained total energy expenditure. This not only questions the validity of the current metabolic limits but also suggests a new perspective on what is physiologically achievable in world-class athletes.